Does allocation of public spending matter in poverty reduction?: Evidence from Thailand - Fan, Shenggen; Yu, Bingxin; Jitsuchon, Somchai (Wiley, 2008)
The present paper uses a panel dataset to estimate the marginal returns to different types of government expenditure on agricultural growth and rural poverty reduction in Thailand. The study finds that additional government spending on agricultural research provides the largest return in terms of agricultural productivity and has the second largest impact on rural poverty reduction. Increased investment in rural electrification has the largest poverty reduction impact, mainly through improved nonfarm employment. Rural education has the third largest impact on both productivity and poverty reduction. Irrigation has a positive impact on agricultural productivity, but regional variation is considerable. Government spending on rural roads has no significant impact on agricultural productivity and its poverty reduction impact ranks last among all investment alternatives considered. Additional investment in the Northeast Region has a greater impact on poverty reduction than in other regions.